Membahas Keadilan dari Balik Bangku Hakim: Tinjauan Terhadap Peran, Tantangan dan Etika dalam Sistem Peradilan - Cindy Kafka Navisa Dewi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Justice is often debated in a legal context, with an emphasis on integrity, procedural fairness and balance of power. This article explains how judges deal with the pressure to ensure justice while overcoming various challenges, including bias, politicization, and external pressure. The role of judges' ethics and social responsibility in maintaining judicial integrity and independence is also discussed. Through this review, it is hoped to gain a deeper understanding of the complexities and challenges faced by judges in ensuring justice in the justice system. The role of judges is not only as enforcers of the law but also as guardians of justice. The challenges judges face include political pressure, difficult decisions, and a changing society. Judges' ethics are key in maintaining the integrity of the justice system, including independence, fairness, and transparency. In addition, to analyze the impact of judges' roles, challenges, and ethical practices on public trust in the justice system. In this context, the main goals are to provide justice to all parties involved, protect human rights, and maintain social order. However, challenges such as corruption, bias and limited resources often stand in the way of achieving these goals. In addition, ethics play a crucial role in maintaining the integrity of the justice system, including principles such as independence, objectivity and transparency.